Assessment of Lung Recruitment by Electrical Impedance Tomography and Oxygenation in ARDS Patients. Issue 22 (May 2016) - Yun, Long; He, Huai-wu; Möller, Knut; Frerichs, Inéz; Liu, Dawei; Zhao, Zhanqi
Abstract : Abstract: We hypothesized that not all patients with appreciably recruited lung tissue during a recruitment maneuver (RM) show significant improvement of oxygenation. In the present study, we combined electrical impedance tomography (EIT) with oxygenation measurements to examine the discrepancies of lung ventilation and perfusion versus oxygenation after RM. A 2-minute RM (20 cm H2 O positive end-expiratory pressure [PEEP] + 20 cm H2 O pressure control) was prospectively conducted in 20 acute respiratory distress syndrome patients from January 2014 to December 2014. A decremental PEEP trial was performed to select the PEEP level after RM. A positive response to RM was identified as PaO2 + PaCO2 ≥400 mm Hg. Relative differences in the distribution of ventilation and perfusion in the most dependent region of interest (ROI4) were monitored with EIT and denoted as the ventilation-perfusion index. Ten patients were found to be responders and 10 patients to be nonresponders. No significant difference in baseline PaO2 /FiO2 was observed between nonresponders and responders. A significantly higher PaO2 /FiO2 ratio during RM and higher PEEP set after PEEP titration were recorded in responders. In both responders and nonresponders, the proportion of ventilation distributed in ROI4 compared with the global value was lower than the cardiac-related activity before RM, but this situation was reversed after RM ( P < 0.01 in each group). Six out of 10 nonresponders exhibited a remarkable increase in ventilation in ROI4. A significant difference in the relative ventilation-perfusion index was found between the patients with remarkable and insufficient lung tissue reopening in the nonresponder group ( P < 0.01). A discrepancy between lung tissue reopening and oxygenation improvement after RM was observed. EIT has the potential to evaluate the efficacy of RM by combining oxygenation measurements.